Transforming the public space to build a citizenship: An experience social cartography and urban acupuncture promoted corporate social responsibility - Graciela Primitz, Ivana (2015)
This research shows methodologies and dynamics to get aims in a region, which were applied in a neighborhood of the city of Córdoba, Argentina. This initiative is part of the Programa de Habitat de la fundacion holcim Argentina, with goal to “improve the lives of families in the areas of influence through the care of the environment and construction - materials and symbolic public spaces which promote a civic culture. The social cartography was used as a tool of participatory urban research where people recognize important places typing on a map of the territory, impressions and suggestions. Through an analysis of sentences written on map, the paper deals with the relations between the subject and the environment as well as systems detect places where people perform their everyday activities. The map identified the social occupation of space in the following areas: ownership on the environment uses spatiotemporal and environmental awareness, facilitating collective interpretation of neighborhood problems. Inserted in a process of urban acupuncture, social cartography has function of producing collective knowledge and became a tool for the projects integrated in the phase of design. In the case of study, it was complemented for an architectural-environmental and a participatory design workshop. with the Technical urban study and ideas in the workshop agreed, desires and demands more decoded from the map, it recovered of the neighborhood square was completed actively involving the community at all levels, showing that it is possible to innovate and create value through interactive processes between public actors, private, academic and community representation in the period of sustainable development.